The duel in early modern England: Civility, politeness, and honour - Peltonen, Markku (Cambridge University, 2013)
Arguments about the duel in early modern England were widespread. To understand duelling is to understand some crucial issues in the cultural and ideological history of Stuart England, and this major new study will engage the attention of a very wide audience of historians, cultural and literary scholars.